Cardiobacterium hominis infective endocarditis: A literature review - Ryohei Ono; Izumi Kitagawa; Yoshio Kobayashi (American Heart Journal Plus, 2023)
Background: Cardiobacterium hominis is a member of the HACEK group, which causes infective endocarditis (IE) but is rarely associated with other infections. It is difficult to biologically identify C. hominis because of its slow growth in culture. However, the clinical features of C. hominis IE remain unclear. Method: We searched the PubMed database for all articles of C. hominis IE published between January 2000 and July 2022. Results: The major clinical features of 44 previously reported cases of C. hominis IE were as follows: the median age was 59 years, of which 36 were men; the initial presenting symptoms were chest discomfort (30 %), followed by fever (27 %), night sweats (20 %), fatigability (18 %), weight loss (16 %), and dyspnea (16 %). Almost half of the patients were febrile upon admission. The major predisposing factors were postsurgical valve treatment (57 %), dental treatment or caries (20 %), and congenital valve abnormality (5 %). The median time to identify C. hominis in the blood culture was 4 days, but the longest time was 42 days. The most commonly infected valve was the aortic valve, and the most common complication was systemic embolism. Surgical treatment was performed in 23 (52 %) patients. The most frequent initial treatment regimen was cephem antibiotics, with a median treatment duration of 6 weeks. The overall mortality and recovery rates of C. hominis IE were 9 % and 91 %, respectively. Conclusion: If C. hominis infection is confirmed, physicians should check for the presence of vegetations of the heart valves and understand these characteristics.